CONCRETE-FILLED TUBULAR COLUMN MADE OF VARIOUS TYPES OF MATERIAL - Jen Hua Ling; Yong Tat Lim; Wen Kam Leong; How Teck Sia (Journal of Civil Engineering, 2023)
Concrete-filled tubes (CFT) are gaining popularity due to their excellent performance under compression. Various materials have been used to produce CFTs. Their behavior varied significantly due to the properties of the materials. In this study, numerous articles related to CFT were reviewed. The effects of carbon steel, stainless steel, fibre-reinforced polymers (FRP), plastic materials, and various kinds of concrete on CFT were observed. The fundamental principles governing the behavior of CFT were then determined. The confinement effect of the tube was the key to the outstanding performance of CFT. CFT performed well when the tube had high compressive strength, elastic modulus, tensile strength, ultimate strain, and corrosion resistance. The concrete with high compressive strength and ultimate strain, as well as low elastic modulus and shrinkage, experienced greater strength enhancement under confinement. Nevertheless, confinement effectiveness was greatly affected by the slenderness ratio. Short CFT subjected primarily to axial loads was preferred.